Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber. Issue 3 (4th March 2018) - Sharma, K.K.; Bhushan, V. Shashi; Rao, Cherukuri Sreenivasa; Reddy, K. Narsimha; Banerjee, Hemanta; Mandal, Swagata; Singh, Balwinder; Battu, R.S.; Jyot, Gagan; Sahoo, S.K.; Mohapatra, Soudamini; Lekha, S.; et al.
ABSTRACT: Multi-location supervised field trials were conducted in India at four locations of the All India Network Project (AINP) on Pesticide Residues to study the persistence, dissipation and risk assessment of flubendiamide and deltamethrin on cucumber ( Cucumis sativus ). Residues of flubendiamide and deltamethrin on cucumber resulting from three spray applications of a combination formulation (flubendiamide 90% + deltamethrin 60%, 150 SC) at recommended (22.5 + 15 g a.i./ha) and double the recommended (45 + 30 g a.i./ha) dose were analysed. On the basis of persistence and dissipation studies, the half- life (T1/2 ) of flubendiamide on cucumber varied from 1.40 to 2.98 (recommended dose) and 1.55 to 2.76 days (double the recommended dose), while that of deltamethrin ranged from 2.5 to 4.9 (recommended dose) and 2.7 to 3.9 days (double the recommended dose) at the four locations. On the basis of supervised field trial data and using OECD calculator, MRLs in the combination product of 3 mg kg −1 for flubendiamide and 1.5 mg kg −1 for deltamethrin has been proposed for consideration by the Food Safety and Standards Authority of India (FSSAI). Codex, EU and EPA have fixed MRL of 0.2 mg kg −1 for flubendiamide and deltamethrin.